Konflik Kewarganegaraan dan Identitas Keagamaan : Solusi dalam Kerangka Hukum Islam - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Istiana Istiana; Annisa Nurrohmah; Muhammad Aldhi A (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The conflict between citizenship and religious identity has become one of the significant social and political challenges in the modern era, especially amidst increasing religious pluralism and globalization. This research aims to analyze these problems within the framework of Islamic law, as well as offering relevant solutions to resolve this conflict. Using a descriptive qualitative approach, this research explores the concepts of citizenship, religious identity, and the interaction between the two in various country contexts, both Muslim and non-Muslim majority. This study also examines concepts in Islamic law such as muwatana (citizenship), ummah (community), and maslahah (public interest) as solutions offered by Islamic law to harmonize citizenship and religious identity. The findings of this research show that Islamic law has the flexibility to be applied in the context of a modern state, by emphasizing justice, equality and respect for human rights. Through these principles, conflicts between citizenship and religious identity can be reduced, both in Muslim-majority countries and in countries with secular policies.